THE ROLE OF TEACHER GUIDANCE IN IMPROVING STUDENT LEARNING OUTCOMES IN MATHEMATICS THROUGH PICTURE MEDIA IN GRADE V OF ELEMENTARY SCHOOL 3, MOROTAI ISLAND - Nurhani Mahmud; Nurhamsa Mahmud (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study aims to determine the learning outcomes of mathematics on cylindrical solids through image media in fifth grade students of Elementary School III of Morotai Island. This type of research is Classroom Action Research (CAR) with 22 students as research subjects. This Action Research was conducted in two cycles consisting of planning, implementation, observation and reflection stages. Data collection techniques through observation and tests and data were analyzed in quantitative form. The results of this study indicate that learning mathematics using image media can improve student and teacher learning outcomes in the teaching and learning process. Student learning outcomes from Cycle I score 41% (9 students) who completed, not completed 59% (13 students) increased and in Cycle II there was an increase in score 86% (19 students) who completed and not completed 14% (3 students) classically learning outcomes have reached the KKM standard of 65.